Madihin in transition: performance, hybridity, and cultural transformation in banjarese oral art - Zakia Sani, Muhammad Budi; Wadiyo, Wadiyo; A Sayuti, Suminto; Syakir, Syakir (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Madihin is a traditional Banjarese oral performance art that combines rhythmic improvisation, poetic verses, humor, and the beating of the tarbang (frame drum). More than mere entertainment, Madihin historically functioned as a medium of advice, social commentary, and community bonding. However, in the context of modernization and globalization, both its functions and modes of presentation have been reshaped. This study aims to analyze the continuity and transformation of Madihin by focusing on its changing functions, performance forms, and cultural significance in contemporary society. Employing a qualitative approach, data were collected through interviews with prominent pamadihinan (performers), field observations, and documentation analysis. The findings reveal that Madihin has shifted from its traditional role as a vehicle of moral counsel and communal entertainment to a more diverse medium encompassing education, tourism promotion, and even political communication. Performance innovations such as Madihin hip-hop and Madihin dangdutillustrate how this oral tradition adapts to popular cultural trends while preserving its improvisational core and symbolic values. At the same time, the challenges of regeneration among younger generations highlight the fragile continuity of this art. This research demonstrates that the sustainability of Madihin relies on its capacity for innovation without losing its cultural identity, offering broader insight into how oral performance traditions negotiate relevance, identity, and authenticity in the face of social and cultural change.